A Study of Alternative Measures in Resolving Cases of Child Sexual Abuse among the Ga Community in Accra, Ghana - Markwei, U.; Tetteh, P.M. (Child Abuse Review, 2021)
Many children continue to be sexually abused worldwide. In Ghana, relatively high Figures of child sexual abuse (CSA) are reported by the police daily. Although there There are laws that seek to protect children from sexual abuse, in reality, there is a wide gulf between legislation and practice. This paper explores why this is so by examining the measures adopted in sanctioning perpetrators of CSA in the Ga community in Ghana. The study uses a qualitative approach to collect data from parents and guardians through in-depth interviews. The study revealed that, generally, traditional rather than legal sanctions are adopted in handling CSA cases. This paper thus interrogates the consequences of the obvious contraventions of the law as traditional interventions are resorted to. We posit that CSA can be minimised only when child protection laws are enforced by the police and victims are reoriented to appreciate the benefits of seeking legal redress. © 2021 John Wiley & Sons, Ltd.
Research Article
Keywords: child sexual abuse; child protection legislation; Ghana